1982
DOI: 10.1007/bf00582393
|View full text |Cite
|
Sign up to set email alerts
|

H+ ion secretion in proximal tubule of low-CO2/HCO 3 − perfused isolated rat kidney

Abstract: Acidification in proximal tubule of the isolated rat kidney, perfused in vitro, was studied by stopped-flow microperfusion techniques, using Sb microelectrodes to measure luminal pH. The kidney was perfused with mammalian Ringer's solution at pH 7.4 buffered by 20 mmol/l phosphate and containing 7.5 g/100 ml bovine albumin, equilibrated with air. Final urine pH was 6.88 +/- 0.5. Steady-state pH in proximal segments was 6.81 +/- 0.03 (n = 80), and acidification half-time (t/2) 7.25 +/- 0.33 (80) s, giving a net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…They have been interpreted previously as representing a measure of passive H ion conductance within the framework of a constant pump/variable leak model . More recently, however, evidence has been adduced showing that most of the leak was due to back flow of H ions through the luminal Na/H exchanger; this would not be a passive conductive process (Schwartz, 1981;Rubio et al 1982). Therefore, we will try to interpret variations of t/2 in terms of a different model based on a simple analogue electrical circuit (see Appendix and Fig.…”
Section: Effect Of Co2 After Carbonic Anhydrase Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been interpreted previously as representing a measure of passive H ion conductance within the framework of a constant pump/variable leak model . More recently, however, evidence has been adduced showing that most of the leak was due to back flow of H ions through the luminal Na/H exchanger; this would not be a passive conductive process (Schwartz, 1981;Rubio et al 1982). Therefore, we will try to interpret variations of t/2 in terms of a different model based on a simple analogue electrical circuit (see Appendix and Fig.…”
Section: Effect Of Co2 After Carbonic Anhydrase Inhibitionmentioning
confidence: 99%
“…As shown above, this rate depends on CO2 hydration in the tubular lumen and reaction of H2CO3 with luminal Na2HPO4. The second column is proton generation by uncatalysed cellular CO2 hydration calculated from 'in vitro' kinetic data (Rubio, de Mello, Mangili & Malnic, 1982). The third column is passive bicarbonate flow from capillary to lumen, which in the steady state could be converted into H2CO3 and recycled into the cell, generating H ions without need of carbonic anhydrase catalysis (Rector, 1973).…”
Section: Effect Of Co2 After Carbonic Anhydrase Inhibitionmentioning
confidence: 99%
“…Acidification and alkalinization half-times are a function of R1, Rs and C. Because the buffer load is imposed by the experimental conditions (luminal phosphate buffer content), C is constant. The conductive H-ion flux through Rs seems to be only a small part of passive backflux of H ion (Rubio et al 1982;Amorena et al 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of this alkalinization has been used as a measure of H-ion efflux from the tubular lumen. Although it has been shown that above pH 6 only a minor component of this 91 A. G. LOPES, G. MALNIC AND N. A. REBOUqAS efflux rate is electrodiffusive (Rubio, De Mello, Mangili & Malnic, 1982), this flux should be increased when an additional mechanism of H-ion transfer, in this case a protonophore (DNP), is introduced into the system. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This effect was independent of filtered load, since it was observed during pump perfusion of proximal tubules. It is interesting to note, however, that in the isolated perfused rat kidney preparation, proximal tubule acidification is maintained to a considerable extent, leading to transepithelial pH gradients near those of normal kidney (lumen pH of 6 8) when perfusion is performed with artificial solutions which do not contain haemoglobin, and even at the Po2 of air, that is, at an oxygen supply which is markedly lower than that found in the 'in vivo' kidney (Rubio, de Mello, Mangili & Malnic, 1982). This is consistent with the well-known observation that RBF exceeds the nutritional needs of the organ.…”
Section: Introductionmentioning
confidence: 99%